Congenital hemifacial hyperplasia - S A Deshingkar; S R Barpande; J D Bhavthankar (Contemporary Clinical Dentistry, 2011)
Congenital hemifacial hyperplasia (CHH) is a rare congenital malformation characterized by marked unilateral overdevelopment of hard and soft tissues of the face. Asymmetry in CHH is usually evident at birth and accentuated with age, especially at puberty. The affected side grows at a rate proportional to the nonaffected side so that the disproportion is maintained thr oughout the life. Multisystem involvement has resulted in etiological heterogeneity including heredity, chromosomal abnormalities, atypical forms of twinning, altered intrauterine environment, and endocrine dysfunctions; however, no single theory explains the etiology adequately. Deformities of all tissues of face, including teeth and their related tissues in the jaw, are key findings for correct diagnosis of CHH. Here an attempt has been made to present a case of CHH with its archetypal features and to supplement existing clinical knowledge.